Pengaruh Pelapisan Pektin Kulit Buah Lemon Lokal Terhadap Viabilitas Benih Timun Apel (Cucumis Sp.) pada Periode Simpan Berbeda - Rizki, Muhammad; Azizah, Elia; Samaullah, H.M. Yamin; Syafi’i, Muhammad; Saputro, Nurcahyo Widyodaru (JURNAL AGROPLASMA, 2024)
High-quality seeds are available for planting, and proper storage is necessary. High-quality seeds can experience deterioration during storage, and one alternative to address this issue is by applying seed coating treatments. The research aims to investigate the effect of local lemon peel pectin coating on the viability of apple cucumber seeds (Cucumis sp) and determine the optimal concentration of lemon peel pectin for seed coating. The experiment was conducted at the Agronomy Laboratory, Faculty of Agriculture, Universitas Singaperbangsa Karawang, from November 2023 to March 2024. The method used was an experimental approach with a Completely Randomized Design (CRD) consisting of 15 treatments with 3 replications: A (0 g + 4 weeks), B (0 g + 8 weeks), C (0 g + 12 weeks), D (0.5 g + 4 weeks), E (0.5 g + 8 weeks), F (0.5 g + 12 weeks), G (1 g + 4 weeks), H (1 g + 8 weeks), I (1 g + 12 weeks), J (1.5 g + 4 weeks), K (1.5 g + 8 weeks), L (1.5 g + 12 weeks), M (2 g + 4 weeks), N (2 g + 8 weeks), O (2 g + 12 weeks). The treatment effects were analyzed using analysis of variance (ANOVA), and if the F-test at the 5% significance level was significant, further Duncan Multiple Range Test (DMRT) was conducted to determine the best treatment. The results showed significant effects on germination capacity, vigor index, and growth rate. The best treatment was found in treatment C (0 g + 12 weeks), which achieved the highest germination capacity of 90.30%, and treatment B (0 g + 8 weeks) had the highest vigor index for seed storage at 76.97%. Keywords: apple cucumber, lemon zest, pectin, seed coating